Synchrovox a methods study - Mauricio, Hilario; Libunao, Eriberto Jr; Ballesteros, Patrick; Banloi, Jethro (College of Engineering, 1987)
Originally, RG Meditron, Inc. has its line of business dealing with the distribution of imported medical equipment. Later on, the company shifted to the production of Synchcrovox which is basically a minus-one/sing-along machine. The move was to grasp the opportunity brought about by the rising Japanese developed Karaoke industry. Success seemed to be iminent as the product immediately gained wide acceptance both here and abroad. On paper, the present production process seems ideal using the basis that it can meet the present demand for the product. However, actual sighting of the process seem to indicate the presence of a flaw somewhere in the production line. This is evidenced by the existence of shelves full of work in process awaiting completion of rework. Although work in process is present in all sections, the encasing section appears to be the "bottleneck" of the production line as more materials are piled up in shelves marked for encasing purposes in relation to other sections. At first, it appears that the cause of such inefficiency is the inconsistency in raw materials' arrival. Since the problem of materials planning and scheduling is beyond the scope of this study, the group deviated from the apparent to look for flaws within the system. And, if detected, these flaws will be attacked for the purpose of improvement thus developing a systematic process. However, all alternatives will be within the bounds of specific criteria and restrictions. In the process of searching for alternatives to further improve the present process, the group analyzed the existing method, looking at the "how's" and "why's" of the system with particular attention to the encasing section as suggested by the company's production engineers. Yet, as the study progressed, the group was lead to believed that the problem was not restricted to the Encasing section alone. Therefore, the group backed-tracked and investigated the specifics of preceeding section searching for answers. And, the moved revealed that the hypothesis was correct and thus the group proceeded to search for alternatives limited not only to the Encasing section, but involving the whole production process. Finally, after studying the present process and believing that it has been well and thoroughly analyzed, the group arrived at several alternatives ranging from the rescheduling of personnel working period and the employment of a new procedure of transporting raw materials from one section to another to the rearrangement of the production area lay-out. In evaluating these alternatives, it was arrived at that there is no specific alternative that can be considered "better" than the other. Instead, all the alternatives seem to compliment each other as one will work and produce results better and faster with the implementation of the other. Also, specifics as to how the alternatives should be implemented were started to facilitate its employment. In addition, the group also suggested certain modifications in the process and its specifics to further enhance a systematic approach to the completion of a unit. Proposals in this area range from the alteration of certain tools used in the assembly to the installation of certain features which is not only connected to the improvement of the process but also beneficial to the workers involved in the assembly as it minimizes the risk of being exposed to occupational hazards.